2021
DOI: 10.21203/rs.3.rs-228165/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AFibNet: An Implementation of Atrial Fibrillation Detection With Convolutional Neural Network

Abstract: Background: Generalization model capacity of deep learning (DL) approach for atrial fibrillation (AF) detection remains lacking. It can be seen from previous researches, the DL model formation used only a single frequency sampling of the specific device. Besides, each electrocardiogram (ECG) acquisition dataset produces a different length and sampling frequency to ensure sufficient precision of the R-R intervals to determine the Heart Rate Variability (HRV). An accurate HRV is the gold standard for predicting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous studies have documented the identification of AF in ECG data using different approaches. For example, Tutuko et al [15] proposed a 1D-DCNN that is able to detect AF in unseen data, differentiating it from normal recordings, with an accuracy of 98.8%. A multilabel (AF vs. normal vs. other arrhythmia) 1D-DCNN reported an AF detection accuracy of 82% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the identification of AF in ECG data using different approaches. For example, Tutuko et al [15] proposed a 1D-DCNN that is able to detect AF in unseen data, differentiating it from normal recordings, with an accuracy of 98.8%. A multilabel (AF vs. normal vs. other arrhythmia) 1D-DCNN reported an AF detection accuracy of 82% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Single-lead ECG may be integrated into a smartwatch wristband, making it widely available, and one study found a high sensitivity (97.7%) albeit a low PPV (40%) validated against an implantable cardiac monitor [26]. Cloud-based AI analysis of wearable ECG may allow continuous updates to the algorithm and facilitate contact with healthcare personnel [27]. Deep learning appears to be a stronger tool than classical machine learning for single-lead ECG analysis including detection of AF [28], and single-lead ECG may play a prominent role in AF detection in the future.…”
Section: Af Detection With Aimentioning
confidence: 99%
“…A DNN architecture is called convolutional neural network (CNN), which is particularly designed for processing time series data such as electrocardiograms (ECGs). Previous studies had used CNNs to detect ECG characteristic waveforms [9], arrhythmia [10,11], atrial fibrillation [12,13], hypertrophic cardiomyopathy [14], and myocardial infarction [15].…”
Section: Introductionmentioning
confidence: 99%